Carbon Nanotube Porins in Amphiphilic Block Copolymers as Fully Synthetic Mimics of Biological Membranes. Issue 51 (17th October 2018) - Sanborn, Jeremy R.; Chen, Xi; Yao, Yun‐Chiao; Hammons, Joshua A.; Tunuguntla, Ramya H.; Zhang, Yuliang; Newcomb, Christina C.; Soltis, Jennifer A.; De Yoreo, James J.; Van Buuren, Anthony; Parikh, Atul N.; Noy, Aleksandr
Abstract: Biological membranes provide a fascinating example of a separation system that is multifunctional, tunable, precise, and efficient. Biomimetic membranes, which mimic the architecture of cellular membranes, have the potential to deliver significant improvements in specificity and permeability. Here, a fully synthetic biomimetic membrane is reported that incorporates ultra‐efficient 1.5 nm diameter carbon nanotube porin (CNTPs) channels in a block‐copolymer matrix. It is demonstrated that CNTPs maintain high proton and water permeability in these membranes. CNTPs can also mimic the behavior of biological gap junctions by forming bridges between vesicular compartments that allow transport of small molecules. Abstract : Carbon nanotube porins in polymersome block‐copolymer membranes mimic the hierarchical organization of biological membranes with nanotube channels, enabling highly efficient transport of water protons and ions through the impermeable membrane barrier. These biomimetic pores enable small molecules to enter the polymersome interior and mimic the behavior of gap junctions by enabling direct content exchange between vesicular compartments.